YOUTH, INNOVATION, AND SPIRITUALITY: THE PILLARS OF UZBEKISTAN'S THIRD RENAISSANCE (Intent Research Scientific Journal, 2025)
This article explores the central role of youth, innovation, and spiritual heritage in shaping Uzbekistan's modern development strategy known as the Third Renaissance. It reflects the intrinsic connection between historical legacy and contemporary progress, emphasizing the nation's collective aspiration to build a prosperous and enlightened future.